Legal Effectiveness of Risk-Based Business Licensing for The Rice Milling Industry in The Sawit District of Boyolali Regency - Adelia Zahra Nugroho; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2025)
Modern business in Indonesia brings both positive and negative impacts, where licensing regulations, such as those stipulated in Law Number 11 of 2020 on Job Creation and Government Regulation Number 5 of 2021, aim to improve a conducive business climate and reduce bureaucracy, but implementation still faces technical obstacles and access inequality that can hinder the achievement of compliance and efficiency. The purpose of this study is to explain about: (1) description of risk-based business licensing in the rice milling industry in Sawit District after the Job Creation Law; and (2) legal effectiveness in the application of rice milling licensing in Sawit District after the Job Creation Law. By analyzing the legal effectiveness of risk-based business licensing for the rice milling industry in Sawit District, Boyolali, with an empirical juridical approach. Based on the research results, out of 26 rice milling industry businesses in Sawit District, 22 do not have a Business Identification Number (NIB), while only 4 have applied for one, with the main obstacles being a lack of understanding of the importance of licensing, limited access to technology, and concerns about additional tax burdens. Although the Online Single Submission (OSS) system has been introduced to simplify the risk-based licensing process, low digital literacy and lack of socialization from local governments are still the main obstacles in improving business compliance with licensing regulations. Legal effectiveness in rice milling licensing in Sawit District is still hampered by the weak legal structure, less than optimal implementation of legal substance, and the low legal culture of the community. Strengthening the role of implementing apparatus, simplifying the licensing mechanism, and more intensive socialization are needed so that the implementation of risk-based licensing can run more effectively and be accepted by the community.